2009
DOI: 10.2527/jas.2009-1790
|View full text |Cite
|
Sign up to set email alerts
|

The caspase proteolytic system in callipyge and normal lambs in longissimus, semimembranosus, and infraspinatus muscles during postmortem storage1

Abstract: The objective of this experiment was to determine whether the caspase proteolytic system has a role in postmortem tenderization. Six ewes and 6 wethers that were noncarriers and 6 ewes and 6 wethers that were expressing the callipyge gene were used for this study. Caspase activities were determined in LM at 7 different time points during the postmortem storage period: 0 h, 4 h, 8 h, 24 h, 2 ci, 7 ci, and 21 cl and in semimembranosus (SM) and infraspinatus (IS) muscles at 0 h, 8 h. 24 h, and 7 d from callipyge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
(26 reference statements)
3
27
0
1
Order By: Relevance
“…Caspase activity changes across the postmortem conditioning period of pork, chicken, and beef, with the highest activities always detected in the early postmortem phase. 8,[28][29][30] Changes in CASP3/caspase 3 and CASP7, as well as CASP9 activity during the early phase of conditioning of porcine LD muscle have been identified to have a negative relationship with shear force; thus, the more caspase activation, the greater the change and the lower the shear force value, and therefore the higher the level of meat tenderness. 8 However, other authors 31 when examining changes in CASP3 activity and protein expression in beef muscle samples during postmortem aging, only detected the inactive isoform of CASP3, not the active one, and no association between caspase isoforms and shear force values was found.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase activity changes across the postmortem conditioning period of pork, chicken, and beef, with the highest activities always detected in the early postmortem phase. 8,[28][29][30] Changes in CASP3/caspase 3 and CASP7, as well as CASP9 activity during the early phase of conditioning of porcine LD muscle have been identified to have a negative relationship with shear force; thus, the more caspase activation, the greater the change and the lower the shear force value, and therefore the higher the level of meat tenderness. 8 However, other authors 31 when examining changes in CASP3 activity and protein expression in beef muscle samples during postmortem aging, only detected the inactive isoform of CASP3, not the active one, and no association between caspase isoforms and shear force values was found.…”
Section: Discussionmentioning
confidence: 99%
“…A negative relationship was also detected between the peak caspase-3/7 activity at 8 h in longissimus muscles from normal lambs and calpastatin activity at 0 day and 2 days (r = -0.65, r = -0.68, respectively, P < 0.05). Again, in our experiment, calpastatin activity decreased with increased time, as found by Kemp et al (2009). This is therefore evidence for the indirect involvement of caspase in post mortem proteolysis and meat tenderisation, although other studies suggest a direct role for caspases and apoptosis in post mortem proteolysis.…”
Section: Discussionmentioning
confidence: 32%
“…Determination of Caspase 3/7 activity. Caspase 3/7 activity was determined in breast muscle samples according to the method of Wagner et al (2003) and Kemp et al (2009). Frozen samples were crushed in liquid nitrogen, and 1 g was homogenised in 3 volumes of extraction buffer [25 mmol/l HEPES (pH = 7.5), 1 mmol/l EGTA, 1 mmol/l EDTA, 0.1% (v/v) Triton X-100, 5 mmol/l MgCl 2 , 2 mmol/l DTT(1,4-dithiothreitol), (ethylene glycol tetra-acetic acid), 74 μmol/l antipain, 20 μmol/l leupeptin, 15 μmol/l pepstatin, 0.15 μmol/l aprotinin] for 2 × 20 seconds.…”
Section: Semi-quantitative Analysis Of Destained Proteinsmentioning
confidence: 99%
“…There is relatively little data, however, on the interaction between caspases and the calpain enzyme system in skeletal muscle as it relates to postmortem proteolysis. A negative relationship between peak caspase 3/7 activity at 8 hours postmortem and calpastatin activity at 0 and 2 days postmortem has been observed in the muscles of normal lambs but not in callipyge lambs (Kemp et al 2009 ). Thus, while there is no direct evidence that caspases contribute signifi cantly to postmortem tenderization, data suggest that they may play an indirect role by degrading calpastatin.…”
Section: Caspasesmentioning
confidence: 99%
“…In this study, pro -caspase 3 was not activated during postmortem storage and caspase 3 activity was not correlated with Warner -Bratzler shear force in beef longissimus . The data from one study using muscle from callipyge and normal lambs indicated that caspase 3/7 and caspase 9 activities decreased between 1 and 21 days postmortem but did not directly support or reject the involvement of the caspase system in meat tenderization (Kemp et al 2009 ).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%